Optimalisasi Digitalisasi Dinas Tenaga Kerja Sebagai Recruitment Management dalam Upaya Mengatasi Pengangguran - Suprayetno Suprayetno; Muhammad Nur Rofiq; Mahrus Mahrus; Muhammad Rizal Hidayatullah; Yenie Eva Damayanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This community service has several objectives, first assistance in making AK1, second, widening the information system regarding job vacancies and the employment ecosystem with a digitalization system and making it more integrated. Carried out using the PAR (Participatory Action Research) method, with several stages, namely, participation, planning, implementation, and evaluation. So that this service produces output from optimizing the digitalization system for job seekers and workers which makes it easier to find various information, and the form of competency training carried out also has a positive impact on companies that want to recruit employees because they have received provisions from the training program that has been held.